Sebuah Penggunaan Penerjemahan pada Kelas Pragmatik STKIP PGRI Sidoarjo: Penerjemahan Bahasa, Pengajaran Siswa EFL Pragmatik, Praktik Penerjemahan di kelas - Yunmar, Kintan Kirana; Sabat, Yuliyanto; Prasetyo, Yudy; Putranto, Henry Rio (BASIS (Bahasa dan Sastra Inggris), 2024)
Abstract This research focused on exploring the usefulness of translanguaging used by pragmatics lecturers in teaching and English learning in EFL classroom at STKIP PGRI Sidoarjo. The grand theory used in this research was translanguaging conception by Cen Williams (1980s). This type of research was qualitative approach using observation. The data of this research were fragmented statements taken from voice recordings and notes concluded by the researcher. The data source was supporting data in the form of visual documents taken from observations, interviews, and documents non-visual taken from the documentation. Data collection techniques in this study were observation, interviews, sound recording and documentation. The data analysis technique in this study was thematic analysis. Based on the analysis, there were 2 findings from the perspective translanguaging practice in English as a Foreign Language class. First, the research results reveal that using Mixed languages ​​keep EFL students motivated to learn languages English better and to be able to achieve their dreams. Second, the results of further research reveal that the use translanguaging makes it easier for lecturers to explain material to EFL students. Keywords: Translanguaging, EFL Learner, EFL Teacher, Pragmatics, Language Translation Practice